Water quality in swamps by evaluating the presence of physical-chemical and biological parameters - Alexander Pérez Cordero; Donicer E.Montes Vergara; Yelitza Aguas Mendoza (International Journal of Medical Toxicology and Legal Medicine, 2024)
The objective of this study was to evaluate the water quality of the San Benito de Abad swamp by analyzing the physicochemical and microbiological parameters present in the water. Initially, a search for scientific information on the current state of contamination was carried out, then a visit and pre-diagnosis of the current state of the water were carried out, and finally, sampling, storage, processing, packaging and chain of custody were carried out for water quality analysis and analysis of the current state compared to the national regulations for surface waters established in Colombia. According to the principal component analysis (PCA), the chemical parameters with the highest values analyzed corresponded to orthophosphate, total phosphorus and total solids, followed by the presence of turbidity, salinity and chlorophyll b. These variables are of great importance for aquatic ecosystems because they are indicative of the composition and dynamics of the polluting agents and contribute to the evaluation of the water quality of lotic bodies.